ASPEK HUKUM GOLONGAN PUTIH DALAM PEMILIHAN UMUM - Ni Putu Noni Suharyanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Ngurah Rai, 2020)
In the implementation of elections in Indonesia, both legislative elections, presidential elections or regional head elections, there is always a phenomenon of white group voters or often known as